2020
DOI: 10.1590/0034-737x202067030008
|View full text |Cite
|
Sign up to set email alerts
|

The use of pre-emergence herbicides in cassava decreases the need of manual weeding

Abstract: Weed management consists of a fundamental practice in cassava, with mechanical and chemical control widely used. The objective of this work was to evaluate the efficacy of pre-emergence herbicides, as well as to determine the interaction of these with weeding complementation in the weed management in cassava. Two experiments were conducted in Junqueiro (Alagoas). In 2015/16, the experimental design was based on randomized blocks, with treatments distributed in a split-split-plot scheme, with four replications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…In the same agroecological zone, Chikoye et al (2007) reported a 54–96% reduction in labor costs from using herbicides to replace manual hoe weeding. Santigo et al (2020) noted that pre-emergence herbicides decreased the need for manual weeding in cassava in Brazil. In Nigeria, the most popular herbicides for this purpose are atrazine, s-metolachlor + atrazine, glyphosate, and paraquat.…”
Section: Introductionmentioning
confidence: 99%
“…In the same agroecological zone, Chikoye et al (2007) reported a 54–96% reduction in labor costs from using herbicides to replace manual hoe weeding. Santigo et al (2020) noted that pre-emergence herbicides decreased the need for manual weeding in cassava in Brazil. In Nigeria, the most popular herbicides for this purpose are atrazine, s-metolachlor + atrazine, glyphosate, and paraquat.…”
Section: Introductionmentioning
confidence: 99%